1994
DOI: 10.1161/01.res.74.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally timed expression of an embryonic growth phenotype in vascular smooth muscle cells.

Abstract: Little is known about the phenotypic changes that occur in vascular smooth muscle cells (SMCs) as the developing aorta undergoes the transition from a loosely organized, highly replicative tissue to a morphologically mature, quiescent tissue. In the present study, we have characterized the in vivo pattern of SMC replication during intrauterine and neonatal aortic development in the rat and have cultured and assessed the in vitro growth properties of embryonic, fetal, and neonatal vascular SMCs. Embryonic SMCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 36 publications
3
67
0
1
Order By: Relevance
“…During late embryogenesis and postnatal development, SMCs have an extremely high rate of proliferation with subsequent rapid induction of multiple SMC differentiation marker genes (28,29). In zebrafish, the high proliferation rate of gut epithelial cells and SMC progenitors between 36 hpf and 74 hpf decreases significantly between 74 and 120 hpf, at a time when miR-145 begins to be expressed (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…During late embryogenesis and postnatal development, SMCs have an extremely high rate of proliferation with subsequent rapid induction of multiple SMC differentiation marker genes (28,29). In zebrafish, the high proliferation rate of gut epithelial cells and SMC progenitors between 36 hpf and 74 hpf decreases significantly between 74 and 120 hpf, at a time when miR-145 begins to be expressed (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…replication in the absence of matrix injury, and that one primary function of this growth-suppressive matrix may be to negatively regulate the expression of transcription factors, such as Oct-1, required for cell replication. In a separate study (Weiser et al, 1996), we have shown that expression of the perlecan gene is developmentally regulated in rat aortic SMCs and is first detectable in SMCs at embryonic day 18, a point in development when SMC replication begins to dramatically decrease (Cook et al, 1994 (Figure 12). In this context, vascular injury may involve physical, proteolytic, or compositional changes in the SMC basal lamina.…”
Section: Role Of Basement Membrane Components Inmentioning
confidence: 93%
“…30 -32 SMC populations with either spindle-shaped or epithelioid phenotypes were isolated from the healthy rat aorta at different ages. 18,19,21,22 In particular, spindle-shaped SMCs were predominant in fetuses at different developmental stages, 22 as well as in newborn (4 to 5 days) 19,21,33 and adult (6 weeks to 3 months) rats, 13,21,34,35 whereas epithelioid SMCs were prevalent in old rats (Ļ¾18 months). 18,21 This suggests that the population of SMCs that exhibit an epithelioid phenotype in vitro increases in rat aortic NM with age.…”
Section: Establishment Of Distinct Smc Populationsmentioning
confidence: 98%
“…13,14,16,18,20,23,[53][54][55] In addition, albeit spindle-shaped, SMCs isolated from rat embryos exhibit serum-independent growth capacity. 22 Epithelioid SMCs produce platelet-derived growth factor (PDGF)-BB, which is a potent SMC mitogen, 16,20,23 and fail to respond to the growth-inhibitory effect of transforming growth factor (TGF)-ā¤. 55 However, the factor(s) responsible for serum independence has never been clearly identified.…”
Section: Features Of Smc Subpopulationsmentioning
confidence: 99%
See 1 more Smart Citation